Temperament of New Zealand and North American Holstein cows maintained in two different feeding strategies - Morales-Piñeyrúa, Jéssica Tatiana; Sant’anna, Aline Cristina [UNESP]; Damián, Juan Pablo (Universidad de la República, Facultad de Agronomía, 2025)
Genetics is a factor that influences the dairy cows’ temperament. The objective of the present study was to compare the responses to different temperament tests of New Zealand (NZ) and North American (NA) Holstein cows maintained in two different feeding strategies. A total of 120 cows from the Experimental dairy farm of the National Agricultural and Livestock Research Institute (in Spanish, INIA, Uruguay) were grouped into two Holstein strains: NZ or NA, and two feeding strategies: Grass Maximum or Grass Fixed. Milking reactivity (MR), Flight speed and Distance (FD) were assessed in two periods (107.5 ± 30.3 and 173.8 ± 32.1 days in milk). The averages of these repetitions were used in general linear models with Holstein strains (NZ vs. NA), parity (primiparous vs. multiparous), feeding system (Grass Maximum vs. Grass Fixed), and all two-factor interactions as fixed effects. For MR, there was an interaction between strains and parity. The difference between NZ and NA was observed only for multiparous cows, with higher MR in NZ (2.93 ± 1.18) than in NA (2.00 ± 0.90) (P=0.0004). The NZ cows had longer FD (4.2 ± 1.3 m) than NA cows (3.7 ± 1.1 m) (P=0.03). Feeding system did not affect the cow’s reactivity. In conclusion, dairy Holstein cows’ genetic strain was a factor related to MR and FD tests. In the milking parlor, multiparous NZ cows were more reactive than NA, which did not happen for the primiparous ones. The NZ cows were more reactive to humans than NA in the paddock, exhibiting longer flight distances.
Temperamento de vacas Holando de origen neozelandés y norteamericano mantenidas en dos estrategias alimentarias diferentes
Temperamento de vacas Holandesas Neozelandesas e Norte-americanas mantidas sob duas diferentes estratégias alimentares
Keywords: biotype; cattle; milk; personality